Naturally occurring dominant resistance mutations to hepatitis C virus protease and polymerase inhibitors in treatment-naïve patients - Kuntzen, Thomas; Timm, Joerg; Berical, Andrew; Lennon, Niall; Berlin, Aaron M.; Young, Sarah K.; Lee, Bongshin; Heckerman, David; Carlson, Jonathan M.; Reyor, Laura L.; Kleyman, Marianna; McMahon, Cory M.; et al. (Hepatology, 2008)
Resistance mutations to hepatitis C virus (HCV) nonstructural protein 3 (NS3) protease inhibitors in <1% of the viral quasispecies may still allow >1000-fold viral load reductions upon treatment, consistent with their reported reduced replicative fitness in vitro. Recently, however, an R155K protease mutation was reported as the dominant quasispecies in a treatment-naïve individual, raising concerns about possible full drug resistance. To investigate the prevalence of dominant resistance mutations against specifically targeted antiviral therapy for HCV (STAT-C) in the population, we analyzed HCV genome sequences from 507 treatment-naïve patients infected with HCV genotype 1 from the United States, Germany, and Switzerland. Phylogenetic sequence analysis and viral load data were used to identify the possible spread of replication-competent, drug-resistant viral strains in the population and to infer the consequences of these mutations upon viral replication in vivo. Mutations described to confer resistance to the protease inhibitors Telaprevir, BILN2061, ITMN-191, SCH6 and Boceprevir; the NS5B polymerase inhibitor AG-021541; and to the NS4A antagonist ACH-806 were observed mostly as sporadic, unrelated cases, at frequencies between 0.3% and 2.8% in the population, including two patients with possible multidrug resistance. Collectively, however, 8.6% of the patients infected with genotype 1a and 1.4% of those infected with genotype 1b carried at least one dominant resistance mutation. Viral loads were high in the majority of these patients, suggesting that drug-resistant viral strains might achieve replication levels comparable to nonresistant viruses in vivo. Conclusion: Naturally occurring dominant STAT-C resistance mutations are common in treatment-naïve patients infected with HCV genotype 1. Their influence on treatment outcome should further be characterized to evaluate possible benefits of drug resistance testing for individual tailoring of drug combinations when treatment options are limited due to previous nonresponse to peginterferon and ribavirin. (HEPATOLOGY 2008;48:1769-1778.)